2022
DOI: 10.1371/journal.pntd.0010176
|View full text |Cite
|
Sign up to set email alerts
|

Host tissue proteomics reveal insights into the molecular basis of Schistosoma haematobium-induced bladder pathology

Abstract: Urogenital schistosomiasis remains a major public health concern worldwide. In response to egg deposition, the host bladder undergoes gross and molecular morphological changes relevant for disease manifestation. However, limited mechanistic studies to date imply that the molecular mechanisms underlying pathology are not well-defined. We leveraged a mouse model of urogenital schistosomiasis to perform for the first time, proteome profiling of the early molecular events that occur in the bladder after exposure t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…Such analysis could however be particularly useful in revealing novel facets of the pathological mechanisms associated with human strongyloidiasis, especially when applied in comparative studies. Indeed, this strategy has already been successfully applied to the study of other helminthiases, including schistosomiasis, fasciolosis and echinococcosis, to identify proteins or biological processes altered in the pathological state compared to uninfected controls, during the disease progression or in response to treatment [66][67][68][69][70][71][72][73][74][75][76]. The most commonly investigated samples are plasma/serum and plasma/serumderived EVs (either from animal models or from patients), even though also tissue proteomics has been described [69,70].…”
Section: Proteomics To Study the Host Response To The Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such analysis could however be particularly useful in revealing novel facets of the pathological mechanisms associated with human strongyloidiasis, especially when applied in comparative studies. Indeed, this strategy has already been successfully applied to the study of other helminthiases, including schistosomiasis, fasciolosis and echinococcosis, to identify proteins or biological processes altered in the pathological state compared to uninfected controls, during the disease progression or in response to treatment [66][67][68][69][70][71][72][73][74][75][76]. The most commonly investigated samples are plasma/serum and plasma/serumderived EVs (either from animal models or from patients), even though also tissue proteomics has been described [69,70].…”
Section: Proteomics To Study the Host Response To The Infectionmentioning
confidence: 99%
“…Indeed, this strategy has already been successfully applied to the study of other helminthiases, including schistosomiasis, fasciolosis and echinococcosis, to identify proteins or biological processes altered in the pathological state compared to uninfected controls, during the disease progression or in response to treatment [66][67][68][69][70][71][72][73][74][75][76]. The most commonly investigated samples are plasma/serum and plasma/serumderived EVs (either from animal models or from patients), even though also tissue proteomics has been described [69,70]. Importantly, a number of studies identified parasite proteins within the host's systemic or vesicular proteome, supporting the relevance of host proteomics also in revealing novel diagnostic markers [67,68,71,72,74,75].…”
Section: Proteomics To Study the Host Response To The Infectionmentioning
confidence: 99%
“…A recent study, performed in murine models, that addressed the proteome tissue profile in the bladder, after egg-injection, also corroborated that this parasitosis may drive to urothelial hyperplasia and further bladder carcinoma. The study revealed a differentiated expression of several proteins associated with carcinogenic pathways, cellular activity and enhancement of immune inflammatory responses involved in granuloma formation, Th2 responses as well as reduced integrity needed for egg shedding ( 37 ). Amongst the proteins associated with malignancy, cell proliferation and cancer poor prognosis was disabled homolog 2 (Dab2) that was reported to be associated with epithelial-mesenchymal transition and tumor aggressiveness in BUC ( 38 ).…”
Section: Bladder Schistosomal Squamous Cell Carcinoma Biomarkers – Fr...mentioning
confidence: 99%
“…Dab2 has a role in the canonical Tumor-Growth-Factor-beta (TGF-β) signaling in fibroblasts and immune tolerance, especially in regulatory-T-cells (Tregs) - mediated immunosuppression and toll-like receptor (TLR) suppression in antigen presenting cells (APCs) ( 39 , 40 ). Other proteins associated with inflammation and tissue repair were also upregulated in bladder-egg-injected tissue, namely, complement component 8 (C8a), platelet endothelial cell adhesion molecule (Pecam1) and serine protease inhibitor A3N (Serpina3n) ( 37 ).…”
Section: Bladder Schistosomal Squamous Cell Carcinoma Biomarkers – Fr...mentioning
confidence: 99%
“…Currently, the only rodent models that recapitulate key features of the urogenital disease observed in human infections involve directly injecting parasite eggs into the bladder wall [25,26] or vaginal wall [27] of mice. Using the bladder wall injection model, studies have explored host responses to the parasite involving: changes in the gene expression profile of the bladder [28]; natural killer T cells and their altered function [29]; macrophages [30]; changes in genome-wide methylation of the bladder [31]; urothelium-specific p53 [32,33]; concurrent natural S. haematobium infection [34]; interleukin-4 signaling [35]; angiogenesis, vascular permeability, and cell proliferation [36]; carcinogenesis during concurrent administration of sub-carcinogenic doses of nitrosamine compounds [37]; and changes in the protein expression profile of the bladder [38].…”
Section: Introductionmentioning
confidence: 99%